Magnetic fields from a scaled down model transmission Line - Simulation and comparison to measurements - Rahman N.A.; Hussain H.; Said I.; Jalal T.S.; Farag A.S. (2023)
The last two decade had witnessed growing public concern over possible harmful effects of electric and magnetic fields emanated from electric power facilities and transmission lines. Numerous works examined magnetic fields emanating from conventionally designed transmission lines had been carried out. As the continuous and quality of supply is of utmost importance, changes to the actual line settings and configurations needed during a study are limited and difficult to make in order not to cause any interruption of supply especially to those sensitive areas. This paper reports the construction of a scaled down double circuit transmission line, the measurement results obtained and results of simulation study in order to assess the performance of an actual double circuit transmission line. It was found that the measured value corresponds well to the simulated value. The optimum phase arrangement is sought in view of the lowest peak magnetic field and the magnetic field at the edge of right-of-way. Others suggested usage of the scaled down model for the reduction of magnetic field such as using passive and active shielding are also presented. 2005 IEEE.